Variation in Patient-reported Outcomes Across Hospitals Following Surgery. Issue 11 (November 2015) - Waljee, Jennifer F.; Ghaferi, Amir; Finks, Jonathan F.; Cassidy, Ruth; Varban, Oliver; Carlin, Arthur; Carlozzi, Noelle; Dimick, Justin
Abstract : Background: Although there is growing interest in applying patient-reported outcomes (PROs) toward surgical quality, the extent to which PROs vary across hospitals following surgical procedures is unknown. Objectives: We examined variation in PROs, specifically health-related quality of life (HRQOL), across hospitals performing bariatric surgery. Research Design: A retrospective cohort study. Subjects: The Michigan Bariatric Surgery Collaborative is a statewide consortium of 39 hospitals performing laparoscopic gastric bypass, gastric banding, or sleeve gastrectomy (n=11, 420 patients between 2008 and 2012). Measures: We examined generic and disease-specific HRQOL measured by the Health and Activities Limitations Index (HALex) and Bariatric Quality of Life index (BQL) preoperatively and at 1 year. We measured the variation in postoperative HRQOL across hospitals, and the effect of risk and reliability adjustment on hospital ranking. Results: In this cohort, HRQOL varied by 56% (HALex) and 37% (BQL) across hospitals. Patient factors accounted for 58% (HALex) to 71% (BQL) of the variation in HRQOL across hospitals. After risk and reliability adjustment, HRQOL varied by 18% (by HALex) and 14.5% (by BQL) across hospitals, and the proportion of patients who experienced a large improvement in HRQOL by HALex ranged from 33% to 69% and 67% to 92% by BQL. After adjusting for patient factors and reliability, these differences diminished to 55%–64% (HALex) and 79%–84% (BQL). Conclusions: Patient factors explain a large proportion of hospital-level variation in PROs following bariatric surgery, underscoring the importance of risk adjustment. However, some variation in PROs across hospitals remains unexplained, suggesting PROs may represent a viable indicator of hospital performance. Abstract : Supplemental Digital Content is available in the text.